2010
DOI: 10.1021/ef901564e
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Heteroatom Compounds in a Crude Oil and Its Saturates, Aromatics, Resins, and Asphaltenes (SARA) and Non-basic Nitrogen Fractions Analyzed by Negative-Ion Electrospray Ionization Fourier Transform Ion Cyclotron Resonance Mass Spectrometry

Abstract: A Liaohe crude oil was separated as saturates, aromatics, resins, and asphaltenes (SARA) and neutral nitrogen fractions. The crude oil and its subfractions were analyzed by negative-ion electrospray ionization (ESI) Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR MS). The results show that neutral nitrogen and acidic heteroatom compounds in the crude oil contain 15-55 carbon atoms with double-bond equivalent (DBE) values of 1-27, containing N

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
321
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 320 publications
(329 citation statements)
references
References 60 publications
8
321
0
Order By: Relevance
“…Each of the four extracts (SFE1, SFE2, SFEN and DCME) was fractionated into saturates, aromatics, resins, and asphaltenes (SARA) fractions by the Chinese Standard Analytical Method for Petroleum and Natural Gas Industry: SY/T 5119-2008 [21].…”
Section: Extraction and Fractionationmentioning
confidence: 99%
See 1 more Smart Citation
“…Each of the four extracts (SFE1, SFE2, SFEN and DCME) was fractionated into saturates, aromatics, resins, and asphaltenes (SARA) fractions by the Chinese Standard Analytical Method for Petroleum and Natural Gas Industry: SY/T 5119-2008 [21].…”
Section: Extraction and Fractionationmentioning
confidence: 99%
“…128 scans of FT-ICR data sets were accumulated to enhance the signal-to-noise ratio and dynamic range. Methodologies for FT-ICR MS mass calibration, data acquisition, and processing were described elsewhere [21,22]. Fig.…”
Section: Esi Ft-icr Msmentioning
confidence: 99%
“…Shi et al (2010a) provided the details of calibration procedure. The peaks in the mass range of 200-800 Da with relative abundance greater than five times the standard deviation of the baseline noise were exported to a spreadsheet.…”
Section: Mass Calibration and Data Analysismentioning
confidence: 99%
“…N1O1 compounds are considered to be intermediates of N1 species biodegradation (Kim et al, 2005). Shi et al (2010a) suggested that the oxygen functional group in the N1O1 compounds is a hydroxyl rather than a cyclic ether group because such compounds are present in polar resin fractions rather than in non-polar aromatic hydrocarbon fractions. In maltene fraction of L-2, N1O1 compounds with DBE values of 10, 13 and 15 are predominant.…”
Section: Parametersmentioning
confidence: 99%
“…Fractionation of maltenes was carried out on a silica/alumina column chromatography. [43][44][45][46] An open glass column of 2 3 60 cm 2 were packed with neutral alumina (200-300 mesh) in its lower half and silica gel (200-300 mesh) in its upper half. Silica gel was washed with toluene/dichloromethane/methanol (1:1:3, v/v) mixture and then dried.…”
Section: Sara Fraction Analysismentioning
confidence: 99%